2018
DOI: 10.1021/acs.macromol.8b00699
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Neutrons along the Polyelectrolyte Complex/Coacervate Continuum

Abstract: The coil size of narrow molecular weight distribution deuterated poly(styrenesulfonate), PSS, within a polyelectrolyte complex doped with KBr was tracked across the continuum from solid to coacervate to solution using small-angle neutron scattering. While PSS alone in solution exhibited the familiar and pronounced "polyelectrolyte effect" of coil shrinkage with increasing [KBr], the radius of gyration R g of the PSS in the complex remained surprisingly constant up to 1.4 M KBr, which is close to the transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 55 publications
11
78
0
Order By: Relevance
“…For example, Fares et al. [ 71 ] found that PDADMA/PSS complex go from solids to coacervates finally to a single‐phase solution with increasing KBr concentration ( Figure ). Fu et al.…”
Section: Macromolecular Coacervationmentioning
confidence: 99%
“…For example, Fares et al. [ 71 ] found that PDADMA/PSS complex go from solids to coacervates finally to a single‐phase solution with increasing KBr concentration ( Figure ). Fu et al.…”
Section: Macromolecular Coacervationmentioning
confidence: 99%
“…40,61 In general, as salt is added and electrostatic interactions are screened, polyelectrolyte chains decrease in effective charge density and more closely resemble neutral polymers in solution by SAXS. 40,42 In our case, we increase both polymer and salt concentrations, in addition to buffer and magnesium amounts, to mimic the impact of drying on the structural level ( Figure 5A). The aim of this experiment was to explore the molecularlevel effects of this realistic environmental change.…”
Section: Comparing the Dried Samples With Composition Mimicsmentioning
confidence: 99%
“…38 Beyond the hydrophilic or hydrophobic aspects of the constituents, which affect phase separation, 39 the coacervate salt content can also impact water retention. [40][41][42] The phase behavior of these systems can be described by diagrams such as ones that relate the polymer concentration in the mixture to that of the salt. [43][44] Choosing a composition is the same as selecting a location on the phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…This review discusses different physicochemical aspects which impact the understanding of the most fundamental bases of the conditioning process.Cosmetics 2020, 7, 26 2 of 21 cationic polyelectrolytes and silicones, onto a surface with a relatively large area (typically~6 m 2 for a head with 20 cm long hairs) [9] which necessitates a careful examination of the physicochemical bases underlying such deposition processes [10][11][12][13][14].Most of the currently used formulations are composed by supramolecular complexes formed by the interaction of cationic polyelectrolytes (namely polycations) and surfactants (mainly negatively charged and zwitterionic). Such supramolecular complexes may appear as soluble complexes or phase-separated systems [15][16][17][18], with the state in which the complexes are found depending on the concentration of compounds involved in the formulation, the temperature and/or the ionic strength. The correct choice of the composition and other variables provides the basis for preparing a one-phase formulation, which can undergo a phase-separation process as result of the dilution process occurring during their application onto the hair fiber under the shower.…”
mentioning
confidence: 99%
“…Most of the currently used formulations are composed by supramolecular complexes formed by the interaction of cationic polyelectrolytes (namely polycations) and surfactants (mainly negatively charged and zwitterionic). Such supramolecular complexes may appear as soluble complexes or phase-separated systems [15][16][17][18], with the state in which the complexes are found depending on the concentration of compounds involved in the formulation, the temperature and/or the ionic strength. The correct choice of the composition and other variables provides the basis for preparing a one-phase formulation, which can undergo a phase-separation process as result of the dilution process occurring during their application onto the hair fiber under the shower.…”
mentioning
confidence: 99%